Factors Affecting Length of Inpatient Forensic Stay: Retrospective Study From Czechia - Páv, Marek; Vňuková, Martina; Sebalo, Ivan (Frontiers in Psychiatry, 2022)
Objectives The length of forensic stay (LoS) is a subject to country-specific legal and service systems. Therefore, the identification of common factors targetable by treatment is at the forefront of forensic psychiatric research. In this study, we present the first reports of forensic characteristics of patients from the Czechia. Methods We conducted a retrospective analysis of data from 260 inpatients discharged from the Bohnice Hospital (Prague) and obtained a set of sociodemographic and clinical variables as well as the Health of the Nation Outcome Scale (HoNOS) and HoNOS-secure scores. Results The following variables were identified as significantly associated with a longer LoS: older age, length of previous psychiatric hospitalization, olanzapine equivalent, clozapine treatment, psychosocial dysfunction, psychotic or paraphilic disorder diagnosis, and sexual offense. A shorter LoS was associated with being in a relationship, being employed before hospitalization, receiving personal support, and committing an index offense under the influence of substance. While the HoNOS score and HoNOS symptom subscale predicted a longer LoS, the HoNOS-secure subscale predicted a shorter stay. Conclusion In the European context, our hospital has a relatively low LoS. The results are consistent with findings linking psychotic disorders and paraphilia with a longer LoS in forensic treatment. Higher doses of antipsychotic medication or clozapine prescriptions were associated with a longer LoS. The results show a high level of unmet needs in this population, highlighting the importance of the availability of follow-up service.